Workplace Inspection System - Zhi Jin, Loo; Kasim, Shahreen (Applied Information Technology And Computer Science, 2022)
A workplace inspection is the process of completely reviewing a workplace for the purpose of identifying and mitigating workplace hazards, as well as ensuring that all requirements are satisfied, and the workplace is safe and risk-free. The result of inspection will decide the safety of workplace and the result is based on workplace checklist. However, the checklist is not checked detail and calculated one by one. The wide scoring range and unclear weightage also will affect the result. Hence, the web-based workplace inspection system with functionality and usability is developed to address the problem. The agile and scrum development is used as methodology and Vue.js, Laravel, Laragon, MariaDB as software requirements in this project. This further indicates that workplace inspection system can be developed to mobile application with further improvements.